Real-Time Flash Glucose Monitoring Had Better Effects on Daily Glycemic Control Compared With Retrospective Flash Glucose Monitoring in Patients With Type 2 Diabetes on Premix Insulin Therapy - Yan, Reng-na; Cai, Ting-ting; Jiang, Lan-lan; Jing, Ting; Cai, Ling; Xie, Xiao-jing; Su, Xiao-fei; Xu, Lan; He, Ke; Cheng, Liang; Cheng, Cheng; Liu, Bing-li; et al. (Frontiers in Endocrinology, 2022)
Background and Aims To compare the effects of real-time and retrospective flash glucose monitoring (FGM) on daily glycemic control and lifestyle in patients with type 2 diabetes on premix insulin therapy. Methods and Results A total of 172 patients using premix insulin, with HbA1c ≥ 7.0% (56 mmol/mol), or the time below the target (TBR) ≥ 4%, or the coefficient of variation (CV) ≥36% during the screening period, were randomly assigned to retrospective FGM (n = 89) or real-time FGM group (n = 83). Another two retrospective or real-time 14-day FGMs were performed respectively, 1 month apart. Both groups received educations and medication adjustment after each FGM. Time in range (3.9 10.0 mmol/l, TIR) increased significantly after 3 months in the real-time FGM group (6.5%) compared with the retrospective FGM group (-1.1%) (p = 0.014). HbA1c decreased in both groups (both p < 0.01). Real-time FGMs increased daily exercise time compared with the retrospective group (p = 0.002). Conclusions Real-time FGM with visible blood glucose improves daily glycemic control and diabetes self-care behaviors better than retrospective FGM in patients with type 2 diabetes on premix insulin therapy. Clinical Trial Registration https://clinicaltrials.gov/NCT04847219.